Geography and trade - Krugman, Paul (Leuven University Press, 1991)
Krugman observes that his own shortcomings in ignoring economic geography have been shared by many professional economists, primarily because of the lack of explanatory models. In Geography and Trade he provides a stimulating synthesis of ideas in the literature and describes new models for implementing a study of economic geography that could change the nature of the field. Economic theory usually assumes away distance. Krugman argues that it is time to put it back - that the location of production in space is a key issue both within and between nations.